Perancangan Interior Henshin Lounge & Bar di Surabaya - Veronica Veronica; Hedy Constancia Indrani; Poppy Firtatwentyna Nilasari (Intra, 2019)
There is still a lack of a place like the Lounge & Bar in Surabaya to accommodate the activities of young executives to socialize comfortably and pleasantly. Lounge & Bar in Surabaya still lacks a distinctive characteristic and attracts the attention of young people to spend their time there. Lounge & Bar in Surabaya has a design that tends to be the same and unattractive, namely a modern minimalist or vintage style with lots of wood material usage. Therefore, with the